Visualization of airborne droplets generated with dental handpieces and verification of the efficacy of high-volume evacuators: an in vitro study - Min Jung Kim; Mana Kuroda; Yoshikazu Kobayashi; Takahisa Yamamoto; Takako Aizawa; Koji Satoh (BMC Oral Health, 2023)
Abstract Background The COVID-19 pandemic led to concerns about the potential airborne transmission of the virus during dental procedures, but evidence of actual transmission in clinical settings was lacking. This study aimed to observe the behavior of dental sprays generated from dental rotary handpieces and to evaluate the effectiveness of high-volume evacuators (HVEs) using laser light sheets and water-sensitive papers. Methods A dental manikin and jaw model were mounted in a dental treatment unit. Mock cutting procedures were performed on an artificial tooth on the maxillary left central incisor using an air turbine, a contra-angle electric micromotor (EM), and a 1:5 speed-up contra-angle EM (×5EM). Intraoral vacuum and extraoral vacuum (EOV) were used to verify the effectiveness of the HVEs. The dynamics and dispersal range of the dental sprays were visualized using a laser light sheet. In addition, environmental surface pollution was monitored three-dimensionally using water-sensitive papers. Results Although the HVEs were effective in both the tests, the use of EOV alone increased vertical dispersal and pollution. Conclusions The use of various types of HVEs to reduce the exposure of operators and assistants to dental sprays when using dental rotary cutting instruments is beneficial. The study findings will be helpful in the event of a future pandemic caused by an emerging or re-emerging infectious disease.